HUBUNGAN KUALITAS LINGKUNGAN PERTEMANAN DENGAN KECENDERUNGAN PENGGUNAAN BAHASA NEGATIF PADA SISWA MAN 1 JAKARTA - Shahwa Ainnun Nisa; Deska Nurdi Nanda; Dania Putri Muthia; Aditya Andung Saputra; Syifa Fauziah; Haekal Nadhil Raziq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between the quality of the friendship environment and the tendency to use negative language among students of MAN 1 Jakarta. This research employed a quantitative approach using a correlational method. The sample consisted of 87 students selected through simple random sampling. Data were collected using Likert-scale questionnaires measuring friendship environment quality and the tendency to use negative language. The collected data were analyzed through validity, reliability, normality, homogeneity, linearity, Kendall's Tau-b correlation, simple linear regression, and coefficient of determination tests. The findings indicated a significant positive relationship between the quality of the friendship environment and the tendency to use negative language, with a Kendall's Tau-b correlation coefficient of 0.248 and a significance value of 0.001. Furthermore, the coefficient of determination (R²) showed that the friendship environment contributed 9.6% to students' tendency to use negative language, while the remaining 90.4% was influenced by other factors beyond this study. These findings suggest that a close friendship environment may encourage the use of negative language as an expression of intimacy rather than hostility.